Haemato-biochemical and mineral status of crossbred cattle from various agroclimatic zones of North-West Himalayan region of Jammu division - SINGH, R; SINGH, V; BAIGH, S A (The Indian Journal of Animal Sciences, 2016)
A baseline survey was conducted to know the status of haemato-biochemical and mineral parameters in crossbred cattle from 3 different agro-climatic zones of Jammu division. Blood samples (301) from cattle of various age groups were collected and analyzed. The average values of Hb, PCV, glucose, TPP, albumin, PUN, Ca, Pi, Mg, Na, K, Fe, Cu and Zn were 8.60 g/dl, 28.82%, 63.97 mg/dl, 6.78 g/dl, 3.16 g/dl, 9.45 mg/dl, 8.64 mg/dl, 4.88 mg/dl, 2.35 mg/dl, 145.63 mEq/I and 4.48 mEq/I, 65.40 µmol/l, 10.89 µmol/l and 31.25 µmol/l, respectively. Based on Hb and PCV level, anaemia was recorded in 28.12 and 18.75% animals, respectively. Overall the plasma analysis revealed deficiency of Ca, Pi, Mg, Na, K, Cu, Zn, Fe among 41.49, 34.27, 3.50, 25.84, 22.09, 48.72, 4.83 and 4.40% cattle population, respectively. Thus, study concludes that area specific mineral mixtures need to be framed and supplemented for enhancing the productive and reproductive potential of crossbred cattle.